Human capital development issues in Malaysia - Roziah Mohd Rasdi; Nor Wahiza Abdul Wahat (Penerbit Universiti Putra Malaysia, 2012)
Human capital development issues in Malaysia ia a book which provides comprehensive review of issues in Malaysia, covering significant human resources development concepts and practices in various contexts including education, youths, employability and the corporate world.